Highly selective cis-1, 4 copolymerization of dienes with polar 2-(3-methylidenepent-4-en-1-yl) pyridine: an approach for recyclable elastomers. Issue 9 (23rd January 2020) - Cai, Ling; Long, Shiyu; Wu, Chunji; Li, Shihui; Yao, Changguang; Hua, Xiufang; Na, Hui; Liu, Dongtao; Tang, Tao; Cui, Dongmei
Abstract : We report the coordination copolymerization of a new polar diene-based monomer (MPEP), with isoprene or butadiene. After being quaternized, the resultant materials exhibit remarkable thermal reshaping and recycling properties. Abstract : Incorporating a polar functional group into macromolecular chains of rubber materials via coordination polymerization is a theoretical challenge. In this work, we report the coordination copolymerization of a new polar diene-based monomer, 2-(3-methylidenepent-4-en-1-yl)pyridine (MPEP), with isoprene or butadiene using a ternary catalytic system composed of bis(phosphino)carbazolideyttriumbis(alkyl) complex, [Ph3 C][B(C6 F5 )4 ] and AlEt3 . The resultant copolymers have high cis -1, 4 regularity (>97%) as well as tuneable polar monomer incorporation ratios. In addition, the pendant polar pyridine groups can be clearly and quantitatively converted into pyridine quaternary ammonium chloride or the iodide salt under mild conditions. Aggregation of the quaternary ammonium salt plays the role of a physical crosslinking joint, which endows the copolymer with high mechanical properties and improved polarity. Moreover, these ionic crosslinking polyisoprene-based elastomers exhibit remarkable thermal reshaping and recycling properties.